2022
DOI: 10.1002/clt2.12150
|View full text |Cite
|
Sign up to set email alerts
|

Contact allergens in moisturizers in preventative emollient therapy – A systematic review

Abstract: Background Results of preventative emollient therapy on atopic dermatitis and food allergy trials are inconsistent. In addition to the ingredients considered beneficial, the moisturizers may contain potentially harmful haptens. This study aimed to assess the prevalence of haptens in moisturizers used in studies to prevent atopic dermatitis or food allergy and assess their correlations to the trial results. Methods A systematic search of studies investigating the role of… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

0
4
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(4 citation statements)
references
References 11 publications
0
4
0
Order By: Relevance
“…Chronic skin exposure to haptens promotes the development of allergic contact dermatitis via the deterioration of the skin barrier and subclinical inflammation, which may facilitate epicutaneous sensitization and promote the development of AD. 31 Although rare, there have also been reports of contact dermatitis secondary to phenoxyethanol exposure. 32 More studies need to properly evaluate the ingredients in emollients.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Chronic skin exposure to haptens promotes the development of allergic contact dermatitis via the deterioration of the skin barrier and subclinical inflammation, which may facilitate epicutaneous sensitization and promote the development of AD. 31 Although rare, there have also been reports of contact dermatitis secondary to phenoxyethanol exposure. 32 More studies need to properly evaluate the ingredients in emollients.…”
Section: Discussionmentioning
confidence: 99%
“…A review of 12 AD prevention trials found that the majority (75%) of preparations contained at least one hapten from which several substances pose high allergic or irritant potential. Chronic skin exposure to haptens promotes the development of allergic contact dermatitis via the deterioration of the skin barrier and subclinical inflammation, which may facilitate epicutaneous sensitization and promote the development of AD 31 . Although rare, there have also been reports of contact dermatitis secondary to phenoxyethanol exposure 32 .…”
Section: Discussionmentioning
confidence: 99%
“…for the prevention of AD, there is a possibility that the use of moisturizing creams for the treatment of already existing AD could have influenced the data. In the opposite case, the path of percutaneous sensitization cannot be excluded, when microparticles of food or other allergens can get into the cream during the application of the emollient to the skin (Ryczaj et al, 2022).…”
Section: Discussionmentioning
confidence: 99%
“…A further issue of compromised skin is the risk of contact allergic dermatitis due to repeated exposure to skin sensitizers [11]. Compared to skin sensitizers commonly found in emollients, which include also lanolin despite its moisturizing quality [45], the risk of skin sensitivity is low when using the calcium vector. The composition of the vector per se, with natural phospholipids, ensures excellent biocompatibility and was well tolerated in the clinical study without any adverse effects.…”
Section: Discussionmentioning
confidence: 99%